Salmonella Biofilm Formation, Chronic Infection, and Immunity Within the Intestine and Hepatobiliary Tract - Harrell, Jaikin E.; Hahn, Mark M.; D’Souza, Shaina J.; Vasicek, Erin M.; Sandala, Jenna L.; Gunn, John S.; McLachlan, James B. (Frontiers in Cellular and Infection Microbiology, 2021)
Within the species of Salmonella enterica, there is significant diversity represented among the numerous subspecies and serovars. Collectively, these account for microbes with variable host ranges, from common plant and animal colonizers to extremely pathogenic and human-specific serovars. Despite these differences, many Salmonella species find commonality in the ability to form biofilms and the ability to cause acute, latent, or chronic disease. The exact outcome of infection depends on many factors such as the growth state of Salmonella, the environmental conditions encountered at the time of infection, as well as the infected host and immune response elicited. Here, we review the numerous biofilm lifestyles of Salmonella (on biotic and abiotic surfaces) and how the production of extracellular polymeric substances not only enhances long-term persistence outside the host but also is an essential function in chronic human infections. Furthermore, careful consideration is made for the events during initial infection that allow for gut transcytosis which, in conjunction with host immune functions, often determine the progression of disease. Both typhoidal and non-typhoidal salmonellae can cause chronic and/or secondary infections, thus the adaptive immune responses to both types of bacteria are discussed with particular attention to the differences between S. Typhi, S. Typhimurium, and invasive non-typhoidal Salmonella that can result in differential immune responses. Finally, while strides have been made in our understanding of immunity to Salmonella in the lymphoid organs, fewer definitive studies exist for intestinal and hepatobiliary immunity. By examining our current knowledge and what remains to be determined, we provide insight into new directions in the field of Salmonella immunity, particularly as it relates to chronic infection.